Tracing the roots of globalization and business principles - Beer, Lawrence A. (International business collection., 2015)
The term globalization is too often defined by the results it produces, both positive and negative, as opposed to being defined as a socially engineered device naturally occurring as civilization progressed. It is a mechanism to manage the affairs of human beings as they provided for their mutual, but not always equal, attainment of satisfaction. It is therefore a universal instrument that emerged out of the ordered exchange process and is to be found in all cultures. Its growth and maturity were fueled by common denominators of value that are shared across and between social groups around the world and act as a trade agent, bridging and bonding alien territories. As such it began in ancient times and continues into the present, where its prevalence has resulted in a more borderless world with increasing interdependence of nations. The historic commercial activities used in the past form the platform of principles still evident in its modern- day structure.